Dual role of Magnesium as a catalyst and precursor with enriched boron in the synthesis of Magnesium diboride nanoparticles. Issue 17 (1st December 2020) - Ahmad, Pervaiz; Khandaker, Mayeen Uddin; Jamil, Saliha; Rehman, Fida; Muhammad, Nawshad; Ullah, Zahoor; Rauf Khan, M. Abdul; Khan, Ghulamullah; Alotaibi, Mshari A.; Alharthi, Abdulrahman I.; Din, Israf Ud; Hussain, Fayyaz; et al.
Abstract : Nano-scale powder of Magnesium (Mg) is found to play the dual role of catalyst and precursor with Boron-10 ( 10 B) in the synthesis of Magnesium diboride nanoparticles (Mg 10 B2 NPs) at 800 °C. Catalytically, Mg softens and melts enriched Boron at a relatively lower temperature than its actual boiling point. As a precursor, it reacts with enriched Boron and forms the Mg 10 B2 compound. The nano-size catalyst and precursors help to grow the as-formed Mg 10 B2 compound in the form of nanoparticles. The shape or morphology of the synthesized Mg 10 B2 NPs is revealed via field emission scanning electron microscopy (FESEM). Energy dispersive x-ray (EDX) spectroscopy has been performed to spot the elemental composition, whereas, X-ray diffraction (XRD), and X-ray photoelectron spectroscopy (XPS) are used to verify the composition and study the phase of the synthesized particles.